Coordinated interaction of Down syndrome cell adhesion molecule and deleted in colorectal cancer with dynamic TUBB3 mediates Netrin-1-induced axon branching. (7th May 2015) - Huang, H.; Shao, Q.; Qu, C.; Yang, T.; Dwyer, T.; Liu, G.
Highlights: DSCAM directly interacts with TUBB3 in a Netrin-1-dependent manner. DSCAM collaborates with DCC in Netrin-1-induced binding to TUBB3. Netrin-1 increases the colocalization of TUBB3 with DSCAM and DCC in axon branches. Netrin-1 induces the interaction of DSCAM with polymerized TUBB3 in MTs. DSCAM, DCC and TUBB3 are required for Netrin-1-induced axon branching. Abstract: Modulation of actin and microtubule (MT) dynamics in neurons is implicated in guidance cue-dependent axon outgrowth, branching and pathfinding. Although the role of MTs in axon guidance has been well known, how extracellular guidance signals engage MT behavior in axon branching remains unclear. Previously, we have shown that TUBB3, the most dynamic β-tubulin isoform in neurons, directly binds to deleted in colorectal cancer (DCC) to regulate MT dynamics in Netrin-1-mediated axon guidance. Here, we report that TUBB3 directly interacted with another Netrin-1 receptor Down syndrome cell adhesion molecule (DSCAM) and Netrin-1 increased this interaction in primary neurons. MT dynamics were required for Netrin-1-promoted association of DSCAM with TUBB3. Knockdown of either DSCAM or DCC or addition of a function blocking anti-DCC antibody mutually blocked Netrin-1-induced interactions, suggesting that DSCAM interdependently coordinated with DCC in Netrin-1-induced binding to TUBB3. Both DSCAM and DCC were partially colocalized with TUBB3 in the axon branch and the axon branching point of primary neurons and Netrin-1 increased these colocalizations. Netrin-1 induced the interaction of endogenous DSCAM with polymerized TUBB3 in primary neurons and Src family kinases (SFKs) were required for regulating this binding. Knockdown of DSCAM only, DCC only or both was sufficient to block Netrin-1-induced axon branching of E15 mouse cortical neurons. Knocking down TUBB3 inhibited Netrin-1 induced axon branching as well. These results suggest that DSCAM collaborates with DCC to regulate MT dynamics via direct binding to dynamic TUBB3 in Netrin-1-induced axon branching.